Health-related benefit claims post-pandemic: UK trends and global context - Eduin Latimer; Freddie Pflanz; Tom Waters (Institute for Fiscal Studies (IFS), 2024)
Individuals in the UK with health conditions may be entitled to two types of benefits - incapacity benefits (for those whose condition prevents them from working) and disability benefits (to help with extra living costs arising from the disability). Since the onset of the pandemic, there has been a substantial increase in the number of individuals claiming these 'health-related' benefits - and official projections suggest that claimant numbers will rise further still. This report explores how the new claimants compare with those who began claims before the COVID-19 pandemic, the geography of new claims, and how the UK's experience compares with that of other developed countries.
Keywords: 330; Government finances and spending; Health and social care; Taxes and benefits; Disability; Employment; Geography; Government spending; Health; Universal credit; Working age benefits